If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + (-2) = 4 + t 9 + -2 = 4 + t Combine like terms: 9 + -2 = 7 7 = 4 + t Solving 7 = 4 + t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. 7 + -1t = 4 + t + -1t Combine like terms: t + -1t = 0 7 + -1t = 4 + 0 7 + -1t = 4 Add '-7' to each side of the equation. 7 + -7 + -1t = 4 + -7 Combine like terms: 7 + -7 = 0 0 + -1t = 4 + -7 -1t = 4 + -7 Combine like terms: 4 + -7 = -3 -1t = -3 Divide each side by '-1'. t = 3 Simplifying t = 3
| 7x+1=31+4x | | 0.60x+.05(4-x)=.10(-20) | | 3(2x+6)=-6 | | 2m-9-8m=27 | | 6-2(4-8x)=2(3x-5) | | 2.5=d-(20) | | x-(3x+7)=11 | | x-6=-12+2x | | 2.5=d-(.20) | | -9+5x=-5x+1 | | 6.8x-15.3+4.2x=6.4+12x | | b=85+(23)w | | x+8=5x+52 | | 7x+19+-2x=55 | | -3x-5=-47+4x | | 5m-2(4m-1)=-14 | | 10=3x-5x+6 | | x-5-8x=16 | | -14x-4(2x-5)=9 | | -x+6+2x=13 | | 18=8-6b | | (30+5x)+(10x+15)=180 | | (x+6)(3x+8)=0 | | -1-5x+3x=1 | | y-5-2=10 | | 12x-13+8=2x | | 4=x+x+2 | | 12x+4-26=-2(3x-82) | | 2y-6x-4=0 | | 10w+5-3w=40 | | 7x-(2x-12)=-8 | | 25x=10-3+5x |